The Origin of Beethoven's Moonlight Sonata - Vogel, Lorenz, 1846-1902 (artist):::Creator::::::::::::
Color woodcut engraving of Beethoven at the piano, based on a painting by Lorenz Vogel, clipping from an unidentified German newspaper.